Pertahanan Diri Korban Kekerasan dalam Relasi Interpersonal : (Studi Kasus pada Karyawan KopiTelu) - Medina Aurelia; Wa Ode Asmawati (International Forum of Researchers and Lecturers, 2024)
Dating is a relationship between two individuals of different sexes sex. Dating doesn't always go well, individuals can't resolving conflicts will use violence as a way out. This research aims to find out the causes and processes why women commit dating violence. This research aims to find out and research the causal factors the occurrence of violence in dating and self-defense of victims of domestic violence in a relationship. This study uses a qualitative method. Data collection carried out by direct interviews with open-ended questions. The research participants numbered eight informants, namely three victims, three perpetrators and two additional informants. Based on the research results, factors were found The occurrence of violence in dating is caused by personal character blaming others, making a big deal out of small things, lack of emotional regulation, as well as selfishness, and excessive thinking. Violent behavior that has been carried out by informants, namely physical violence in the form of kicking, slapping, as well as hitting and in the form of psychological violence in the form of calls bad, forcing, threatening, humiliating, cursing and shouting.